Distal myopathy with rimmed vacuoles: Spectrum of GNE gene mutations in seven Chinese patients - Su, Feifei (Exp Ther Med, 2018)
Distal myopathy with rimmed vacuoles (DMRV) is a rare, autosomal, recessive inherited disease caused by mutations in the GNE gene. DMRV is an adult-onset disorder characterized by progressive muscle atrophy and weakness, which initially involves the distal muscles with quadriceps sparing. To date, >150 GNE mutations have been reported in different populations from around the world. The present study investigated the clinical, pathological and genetic characteristics of seven unrelated DMRV patients from China. Genetic analysis in these patients revealed three novel mutations (c.455_456insC, p.P421L, and p.A287T) and five previously reported mutations (p.D207V, p.C44S, p.G576R, p.A669P, and p.D218G). In addition, the literature on DMRV was reviewed to provide an overview of the disease and broaden the mutational spectrum of the GNE gene in China.